Analisis Kesalahan Siswa dalam Menilai Kebenaran Suatu Pernyataan - Yayan Eryk Setiawan (Didaktik Matematika, 2020)
The reasonings students provided in assessing the truth of a statement still show many mistakes. Therefore, this present research aimed to find the students errors in judging the truth of a statement. The present research employed a qualitative approach, and the participants were 10th-grade senior high school students in one of Lumajang district. This research instrument consisted of three questions demanding evaluative abilities. The findings showed that the students made three kinds of errors reasoning in judging the truth of the statements, which are conceptual errors, principle errors, and factual errors. This study is implied to the Mathematics teachers to provide students opportunities to construct definitions, distinguish the differences among the characteristics of two and three-dimensional figures, and to explain the meaning of mathematical symbols in various contexts to avoid conceptual errors, principle errors, and factual errors.